2019
DOI: 10.1007/s40675-019-00158-7
|View full text |Cite
|
Sign up to set email alerts
|

Update on the Treatment of Idiopathic Hypersomnia

Abstract: Purpose of Review Idiopathic hypersomnia is an incapacitating disorder with a profound impact on daytime performance and quality of life. The most commonly used treatment modalities are lifestyle advice and pharmacological therapy. We present an update on the evidence concerning treatment options for idiopathic hypersomnia. Recent Findings Evidence for non-pharmacological interventions is lacking; improvement in symptoms on introducing these interventions is often less pronounced than in narcolepsy. Additional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
(48 reference statements)
1
4
0
Order By: Relevance
“…12 , 14 In clinical practice prior to the approval of LXB for the treatment of idiopathic hypersomnia in the United States, patients with idiopathic hypersomnia may have taken more than 1 off-label medication to manage their idiopathic hypersomnia symptoms, 45 or cycled through multiple off-label treatments sequentially due to lack of efficacy. 22 , 23 In the present study, similar efficacy was seen between participants entering and maintaining concomitant treatment with alerting agents (traditional stimulants or wake-promoting agents) and participants who were treatment naive, indicating that LXB may be useful as first-line therapy as a single agent, or in combination with alerting agents.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…12 , 14 In clinical practice prior to the approval of LXB for the treatment of idiopathic hypersomnia in the United States, patients with idiopathic hypersomnia may have taken more than 1 off-label medication to manage their idiopathic hypersomnia symptoms, 45 or cycled through multiple off-label treatments sequentially due to lack of efficacy. 22 , 23 In the present study, similar efficacy was seen between participants entering and maintaining concomitant treatment with alerting agents (traditional stimulants or wake-promoting agents) and participants who were treatment naive, indicating that LXB may be useful as first-line therapy as a single agent, or in combination with alerting agents.…”
Section: Discussionsupporting
confidence: 70%
“…Even physicians who may have experience using SXB or LXB in patients with narcolepsy likely had less familiarity with treatments for idiopathic hypersomnia, as there were no FDA-approved therapies for idiopathic hypersomnia at the time of the study. 22 , 23 Finally, it has been demonstrated previously that while many participants with narcolepsy showed a clinically meaningful response to SXB within 2 months, on average, a period of over 3 months is required to reach the maximum therapeutic response to SXB in terms of EDS. 24 …”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…31 However, these symptom management options do not appear to be as effective as they are in people with narcolepsy; for example, intentional napping during the day is typically unrefreshing for people with idiopathic hypersomnia. 1,19,31,33 Collectively, these results underscore that there was an unmet need for therapies with better efficacy. At the time of this study, there were no approved treatments for idiopathic hypersomnia.…”
Section: Discussionmentioning
confidence: 88%
“…Non-pharmacological interventions include avoiding even slight sleep deprivation, keeping a light/dark cycle, maintaining a regular nocturnal sleep schedule, general self-care, and sleep hygiene. However, up to now, these measures have not shown scientific evidence of benefit [ 10 ]. Regardless, a study survey conducted in 2017 found that 96% of participants with self-reported IH used non-pharmacological strategies, including caffeine (82%), daytime naps (81%), scheduled nighttime sleep (75%), exercise (58%), temperature control (47%), and diet (40%) [ 11 ].…”
Section: Discussionmentioning
confidence: 99%